2018
DOI: 10.1155/2018/2101906
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Porcine PBMCs Reveals the Immune Cascade Response and Gene Ontology Terms Related to Cell Death and Fibrosis in the Progression of Liver Failure

Abstract: Background The key gene sets involved in the progression of acute liver failure (ALF), which has a high mortality rate, remain unclear. This study aims to gain a deeper understanding of the transcriptional response of peripheral blood mononuclear cells (PBMCs) following ALF. Methods ALF was induced by D-galactosamine (D-gal) in a porcine model. PBMCs were separated at time zero (baseline group), 36 h (failure group), and 60 h (dying group) after D-gal injection. Transcriptional profiling was performed using RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…immune response (Zhang et al, 2018;Hassan et al, 2022). Furthermore, transcriptomic studies of human peripheral blood mononuclear cells (PBMCs) showed that immunometabolic disorders constitute the core axis of ACLF development (Li et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…immune response (Zhang et al, 2018;Hassan et al, 2022). Furthermore, transcriptomic studies of human peripheral blood mononuclear cells (PBMCs) showed that immunometabolic disorders constitute the core axis of ACLF development (Li et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…New strategies for disease diagnosis and treatment can be developed by decoding genome structure and function, rebuilding gene interaction networks and identifying new biomarkers ( Jiang et al, 2015 ). Previous animal studies based on transcriptional profiling revealed that the progression of liver failure was related to the immune response ( Zhang et al, 2018 ; Hassan et al, 2022 ). Furthermore, transcriptomic studies of human peripheral blood mononuclear cells (PBMCs) showed that immunometabolic disorders constitute the core axis of ACLF development ( Li et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%